HOUSEWIVES EMPOWERMENT THROUGH WASTE RECYCLE BAGS TRAINING - Ajija, Shochrul Rohmatul; Rumayya; Rahmawati, Yessi; Munawaroh, Siti; Fitriyana, Zidna; Setyorini, Wahyu; Alif, Pevi; Sellawati, Mei (Universitas Airlangga, 2024)
The Garbage Bank is a strategy for implementing the Reduce, Reuse, Recycle (3R) principles in waste management in society. Airlangga University through the community program held a Garbage Bank activity located in RT 20 Tanah Kali Kedinding Village. This activity was attended by ten participants from housewives in the area. Since 2020, the Garbage Bank in this area has been carried out, however it still needs a follow-up community service programs so that the Garbage Bank becomes more representative and productive. The Surabaya City Government's policy that prohibits the use of plastic bags in shops/malls provides an opportunity for the Kali Kedinding Land Waste Bank Manager to process inorganic waste into useful and economically valuable items such as shopping bags. In this regard, housewives as waste bank managers also have a strong will to manage inorganic waste. However, there are several problems related to the development of expertise in making shopping bags from inorganic household waste. Not all housewives have a good understanding of using inorganic waste and processing it into shopping bags that have a sale value. Based on these problems, this community service program is directed at providing training on sewing bags from inorganic household waste, training on selling products online through marketplaces, training on business financial management, and training on business organizational governance. The training was conducted in four meetings with a different topic each week. It is hoped that this program can increase awarness about waste management and improve the community's economy. This is in accordance with the indicators of the Sustainable Development Goals (SDGs), namely increasing economic growth, productive employment opportunities, and decent work for the community, and focusing on the efficient use of resources, minimizing waste, and increasing the production of recycled waste in the environment.